Perilaku Kecurangan Akademik Mahasiswa Akuntansi: Dimensi Fraud Diamond - Dewi, I Gusti Ayu Ratih Permata; Pertama, I Gde Agung Wira (Jurnal Ilmiah Akuntansi, 2020)
Academic cheating behavior is the seeds of bigger cheating practices in the future because it can cause more serious problems, such as violations of professional ethics or the occurrence of crimes. This study aims to analyze the influence of fraud risk factors based on the Fraud Diamond perspective, namely pressure, opportunity, rationalization, and competence on the accounting student academic fraud behavior. Data were collected using a questionnaire on 385 accounting students at universities in Bali Province. The data analysis technique used in this research is descriptive statistical analysis and hypothesis testing using multiple linear regression analysis. The results of the study provide evidence that the factors of pressure, opportunity, rationalization, and ability have a positive effect on academic fraud behavior in accounting students.